COAST: A Comprehensive Older-Adult Screening Tool - Karima Alabasi; Nancy J. Gal; Wendy Dahl (EDIS)
Nutrition risk screening is a first step to quickly identify individuals who might be malnourished or at risk of malnutrition. A malnutrition screening tool should be easy to use, quick to administer, and valid—able to correctly identify those at risk of malnutrition. The Comprehensive Older Adult Screening Tool (COAST) is a valid and practical tool to determine if community-dwelling older adults, specifically older adults of lower socioeconomic status, are at risk for malnutrition. This new 6-page publication of the UF/IFAS Food Science and Human Nutrition Department, written by Karima Alabasi, Nancy J. Gal, and Wendy J. Dahl, provides an introduction to COAST as well as the 5-question screening tool. https://edis.ifas.ufl.edu/fs393